1983
DOI: 10.2307/3898171
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Carbohydrate, Nitrogen Contents, and Regrowth of Tall Fescue Tillers

Abstract: Nitrogen and water-soluble carbohydrate contents of Kentucky 31 tall fescue (Festuca arundinaceae Schreb) tillers were determined on a regrowth following clipping to a 25cm stubble. There was a sharp decline in water-soluble carbohydrates of tillers as a result of clipping and N fertilization. Dry matter N content increased during the same time. The reduced carbohydrate content for clipped tillers lasted for some 10 days following clipping. After the initial decrease, water-soluble carbohydrate content in till… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Both forage NDF and ADF were negatively correlated with concentrations of most NSC components. Bahrani et al (1983) reported that N concentration of tall fescue (Kentucky 31) tiller bases 10 d following clipping (around early October in Athens, GA) was linearly and negatively correlated with water‐soluble carbohydrate concentration. In our study, forage CP content was positively correlated with total NSC concentration across the 13 cool‐season grass entries of five species at preheading.…”
Section: Resultsmentioning
confidence: 99%
“…Both forage NDF and ADF were negatively correlated with concentrations of most NSC components. Bahrani et al (1983) reported that N concentration of tall fescue (Kentucky 31) tiller bases 10 d following clipping (around early October in Athens, GA) was linearly and negatively correlated with water‐soluble carbohydrate concentration. In our study, forage CP content was positively correlated with total NSC concentration across the 13 cool‐season grass entries of five species at preheading.…”
Section: Resultsmentioning
confidence: 99%
“…Forage production on the continuously clipped treatment was 40-65% lower compared to the control when the same plots were clipped in May of the next growing season. Severe defoliation often affects the ability of plants to regrow by reducing carbohydrate reserves (Menke and Trilica 1981, Bahrani et al 1983, Richards and Caldwell 1985. Severe defoliation coupled with winter respiration affected the ability of the plants to regrow the next growing season reducing total forage production.…”
Section: Defoliation and Yieldmentioning
confidence: 99%